Arthritis Associated with Crohn's Disease. (1st December 1990) - Gilvarry, JM; Keeling, F; Fitzgerald, O; Fielding, JF
Abstract : A controlled prospective study was undertaken to determine the incidence and characteristic features of peripheral arthritis, sacroiliitis, ankylosing spondylitis and hypertrophic osteoarthropathy in a group of patients with Crohn's disease, and to define the relationship of such arthritides with disease site, duration and activity. Peripheral arthritis occurred in 14.5% of the patients; it was not seen in the control group. This arthritis, which tended to be pauciarticular, was more common in females with large bowel disease and post dated the bowel symptoms in all but one patient. There was close correlation with disease activity. Radiographic sacroiliitis occurred in 12.7% of the patients and ankylosing spondylitis in 7.3%; neither of these were seen in the control group. Sacroiliitis was more common in females and showed no correlation with either disease activity or human lymphocyte antigen (HLA) B27. Ankylosing spondylitis was seen equally in males and females and showed close correlation with both disease activity and HLA B27. Hypertrophic osteoarthropathy occurred in 9.1% of patients. It was not seen in the control group. All patients were asymptomatic. It showed no correlation with disease activity, finger clubbing, age of disease onset, or HLA B27.